Virtual Reality Improves Clinical Assessment of the Optic Nerve - Chen, Elizabeth; Luu, Wilson; Chen, Rosalie; Rafik, Ahmed; Ryu, Yo; Zangerl, Barbara; Kim, Juno (Frontiers in Virtual Reality, 2020)
The most common approach to documenting the optic nerve head (ONH) in the detection and management of glaucoma relies on frontal stereoscopic images acquired by a fundus camera. Subjective clinical assessment of ONH parameters from these images (e.g., cup/disc ratio and cup depth) is limited by the absence of monocular perspective cues normally available in oblique viewing. This study examined whether viewing a rotatable 3D reconstruction of the ONH could improve the accuracy of subjective assessments by increasing linear perspective information. Images were reconstructed from optical coherence tomography (OCT) of the ONH. Trained optometry students assessed the cup/disc (C/D) ratio of ONHs with either a flat stereoscopic display or virtual reality (VR) head-mounted display (HMD) with or without dynamic tilt control. Dynamic stereoscopic assessment of optic nerve head models in VR resulted in larger estimates of C/D ratio and cup depth compared to static stereoscopic assessments. A follow-up experiment using an external display revealed that relative to static monoscopic viewing, adding either dynamic viewing or stereoscopic viewing to the same display improved subjective estimates of C/D ratio relative to Cirrus HD-OCT defined objective values of C/D ratio. The findings suggest that simply changing the viewing orientation of ONH models improves clinical evaluation of C/D ratio by generating perspective cues to depth without the need for stereo viewing.